Team leaders' beliefs about teachers' learning-path strategies. Issue 5 (9th July 2018) - van Bussel, Janne; Justice, Sean; Bang, April; Damirón-Alcántara, Aquiles
Abstract : Purpose: This paper aims to focus on professional development in the education sector. Its goal is to understand team leaders' roles in teachers' professional learning. Second, this paper seeks to understand the influence that team leaders have on teachers' learning path strategies. Design/methodology/approach: Following from van der Krogt's (2007a) Learning Network Theory (LNT), this paper presents a qualitative study of teachers' preferences for specific learning path strategies. Interview data were collected from teachers ( N = 24) and team leaders ( N = 5) at an intermediate vocational school in the Netherlands. Research questions ask to what extent teachers learning path strategies align with the learning path strategies that their team leaders think they should use, and about the influence team leaders have on teachers' professional development. Findings: Findings suggest that teachers and team leaders' beliefs about learning path strategies differ greatly, and that team leaders have limited influence on the learning path strategies that teachers adopt. On the other hand, team leaders appear able to create conditions in which teachers can pursue professional learning because they do have influence on learning facilities. Originality/value: These findings add to the scarce empirical evidence regarding LNT, learning path strategies and team leaders beliefs about teachers professional development. They also imply practical changes for team leaders who want to influence teacher professional development.